Are AuPdTM (T = Sc, Y and M = Al, Ga, In), Heusler compounds superconductors without inversion symmetry? - Kautzsch, Linus; Mende, Felix; Fecher, Gerhard H.; Winterlik, Juergen; Felser, Claudia (Materials, 2019)
Heusler compounds with 2:1:1 stoichiometry either have a centrosymmetric Cu2MnAl structure or an Li2AgSb structure without a centre of inversion. The centrosymmetry is always lost in quaternary Heusler compounds with 1:1:1:1 stoichiometry and LiMgPdSn structure. This presents the possibility of realizing non-centrosymmetric superconductors in the family of Heusler compounds. The objective of this study is to search for and investigate such quaternary derivatives of Heusler compounds, particularly with respect to superconductivity. Several compounds were identified by carrying out calculations from first principles and superconductivity was observed in experiments conducted on AuPdScAl and AuPtScIn at the critical temperatures of 3.0 and 0.96 K, respectively. All investigated compounds had a valence electron count of 27, which is also the case in centrosymmetric Heusler superconductors.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Electronic structure; Heusler compounds; Non-centrosymmetric; Superconductivity